(untitled) (مجلة المنصور, 2023)
In this paper, we will study [Lee, Kim and Yoo, a verifier password typed key agreement] scheme and demonstrate that the scheme is not secure. Then, the authors will propose an enhanced verifier typed key agreement scheme relied on [Lee, Kim and Yoo] scheme and demonstrate that the propose scheme resists against password guessing attack and stolen verifier attack. [The authors are] claimed that the proposed scheme is more secure and efficient compare with [Lee, Kim and Yoo] which is still existed protocol.